PENGELOLAAN FASILITAS OBJEK WISATA PEMANCINGAN POYOTOMO KABUPATEN BINTAN PROVINSI KEPULAUAN RIAU - Endang Sulistiya Ningsih; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Management means a process, method, actions of the manager, the process of carrying out certain activities by moving the power of others, a process that provides oversight of all things involved in implementing policies and achieving goals. This research was conducted at Pemancingan Poyotomo Tourism Object, Bintan Regency, Riau Islands Province. This research aims to determine the general description of facilities at Pemancingan Poyotomo Tourism Objects and to know the process of facility management at Pemancingan Poyotomo Tourism Object, Bintan Regency, Riau Island Province. Qualitative methode was used in this to obtain the full picture occurs in Pemancingan Poyotomo Tourism Object, Bintan Regency, Riau Island Province where researchers tried to describe the actual condition or state by collecting data and information in the field and data collection techniques in this study using observation, interviews and documentation. Based on the research that has been done, the facility management of Pemancingan Poyotomo Tourism Object has not gone well due to some poorly maintained facilities. Keywords : Management, Facility and Pemancingan Poyotomo